Microwave-Assisted Extraction Combined with In-Capillary [Fe(ferrozine)3]2+-CE-DAD to Screen Active Components with the Ability to Chelate Ferrous Ions from Flos Sophorae Immaturus (Flos Sophorae) - Tao Liu; Shanshan Wang; Huifen Ma; Hua Jin; Jin Li; Xuejing Yang; Xiumei Gao; Yanxu Chang (Molecules, 2019)
An efficient microwave-assisted extraction (MAE) combined with in-capillary [Fe(ferrozine)3]2+-capillary electrophoresis-Diode Array Detector (in-capillary [Fe(ferrozine)3]2+-CE-DAD) was developed to screen active components with the ability to chelate ferrous ions and determine the total antioxidant activity. The MAE conditions, including methanol concentration, extraction power, extraction time, and the ratio of material to liquid, were optimized by an L9(34) orthogonal experiment. Background buffer, voltage, and cartridge temperature that affect the separation of six compounds were optimized. It was found that rutin and quercetin were the main components chelating ferrous ions in Flos Sophorae Immaturus (Flos Sophorae) by the in-capillary [Fe(ferrozine)3]2+-CE-DAD. The recoveries were ranged from 95.2% to 104%. It was concluded that the MAE combined with in-capillary [Fe(ferrozine)3]2+-CE-DAD method was a simple, reliable, and efficient tool for screening active components from the complex traditional Chinese medicine samples and evaluating their ability to chelate ferrous ions.